Penyidikan Tindak Pidana Korupsi Pengadaan Barang dan Jasa (Studi Kasus Satuan Reskrim Unit Tipidkor Polrestabes Makassar) (LEGAL DIALOGICA, 2025)
The aim of this research is to improve the performance of law enforcement and the results of this research can provide recommendations for increasing the effectiveness of mechanisms for disclosing criminal acts of corruption Procurement of goods and services for the Criminal Investigation Unit of Makassar Police Tipidkor Unit. And the aim of improving government policy from the results of this research can provide input for improving government policy regarding the prevention and disclosure of criminal acts of corruption both at the local level, including regulations that support law enforcement efforts. To understand and analyze the legal basis for perpetrators of criminal acts of corruption, the legal basis is in Law Number 8 of 1981 concerning criminal procedure law, Law Number 28 of 1999 concerning the Administration of a State that is free from Corruption, Collusion and Nepotism, Law Law Number 31 of 1999 concerning Eradication of Corruption Crimes. The results obtained from this research indicate that investigations into criminal acts of corruption, procurement of capital expenditure, procurement of school praga/practical equipment (shopping for practical equipment for students in the maritime sector), construction of fishing training vessels by the South Sulawesi Provincial Education Service, Makassar Police have handled 1 case since The last 4 years (2020-2024) and there are 4 suspects. The suggestion from the results of this research is that by looking at the implementation of police authority in investigating criminal acts of corruption in the procurement of goods and services at the Makassar police station as it is now, it is in accordance with the laws and regulations that apply to the police. It is hoped that in carrying out future investigations special regulations will be formed in the procurement of goods and services. services provided by the police and given special provisions regarding investigation procedures and authority for coercive measures such as arrest, detention, search and confiscation so that investigators can carry out them effectively within a limited period of time and increase their competence in order to handle corruption cases in the procurement of goods and services effectively, regulations are formed so that police investigators can have special authority in corruption cases so that every member of the public actively participates in providing information as informants or as witnesses to make active reports to the police.Abstrak:Tujuan dari penelitian ini adalah untuk peningkatan kinerja penegakan hukum dan hasil penelitian ini dapat memberikan rekomendasi untuk meningkatkan efektivitas mekanisme pengungkapan tindak pidana korupsi pengadaan barang dan jasa satuan reskrim unit tipidkor polrestabes makassar. Dan bertujuan pebraikan kebijakan pemerintah dari hasil penelitian ini dapat memberikan masukan untuk perbaikan kebijakan pemerintah terkait pencegahan dan pengungkapan tindak pidana korupsi baik di tingkat lokal termasuk regulasi yang mendukung upaya penegakan hukum. Untuk memahami dan menganalisis dasar hukum bagi pelaku tindak pidana korupsi, dasar hukumnya berada pada Undang-Undang Nomor 8 Tahun 1981 tentang hukum acara pidana,Undang-Undang Nomor 28 Tahun 1999 tentang Penyelenggaraan Negaa yang bebas dari Korupsi,Kolusi,Dan Nepotisme, Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi. Hasil yang diperoleh dari penelitian ini menunjukkan bahwa Penyidikan Tindak Pidana Korupsi Pengadaan Belanja Modal Pengadaan Alat-Alaat Praga/Praktek Sekolah (Belanja Peralatan Praktek Siswa Bidang Kemaritiman) Pembuatan Kapal Latih Penangkapan Ikan Oleh Dinas Pendidikan Provinsi Sulawesi Selatan Polrestabes Makassar telah menangani sebanyak 1 kasus sejak 4 tahun terkahir (2020-2024) dan mempunyai 4 orang tersangka. Saran dari hasil penelitian ini adalah dengan melihat pelaksanaan kewenangan polisi dalam penyidikan tindak pidana korupsi pengadaan barang dan jasa di polrestabes makassar seperti sekarang ini adalah sesuai dengan Peraturan Perundang-Undangan yang berlaku untuk pihak kepolisian diharapkan dalam melakukan penyidikan kedepanya dibentuk peraturan khusus dalam pengadaan barang dan jasa yang dilakukan oleh pihak kepolisian dan diberi ketentuan khusus mengenai prosedur penyidikan serta wewenang dalam upaya paksa seperti penangkapan,penahanan,penggeledahan,dan penyitaan agar penyidik dapat melaksanakan secara efektif dalam jangka waktu yang terbatas dan melakukan peningkatan kompetensi agar dapat menangani perkara korupsi dalam pengadaan barang dan jasa dengan efektif,dibentuknya peraturan agar penyidik kepolisian dapatmemiliki wewenang khusus dalam perkara korupsi agar setiap masyarakat berpartisipasi aktif dalam menyampaikan keterangan sebagai informan maupun sebagai saksi untuk melakukan laporan aktif ke kepolisian.Kata Kunci: Penyidikan, Tindak Pidana Korupsi Pengadaan Barang Dan Jasa